Potensi Pemanfaatan Kulit Jeruk Lemon Afkir (Citrus limon (L.) var. Eureka) sebagai Bahan Pembuatan Minyak Asiri - Andri Permana; Sarifah Nurjanah; S Rosalinda; Farah Nuranjani (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Unutilized (off-grade) lemon with slight damage have been utilized for lemon juice, even most of that just become waste. In fact, lemon by-product also have many essential compounds. This research aimed to determine the potential and optimal conditions of unutilized lemon peels using distillation process. The research used experimental methods with a factorial complete randomized design. This research used 3 factors including the conditions of material, distillation methods, and time of distillation. Essential oils parameters observed included oil yield, volatile compounds, and physico-chemical characteristics. Based on the results of research, unutilized lemon produced a concentration of limonene compounds of 63,8—67,7%. Optimal treatment was found in the fresh material, using steam and hydro distillation for 6 hours that produced an oil yield of 0.25%, a specific gravity of 0.856 g/ml, an acid value of 2.749 mg KOH/g, and an odour close to fresh lemon peel.